Islamic Banking - Mirakhor, Abbas (Occasional Papers; Occasional Paper, 1987)
This study was prepared by Zubair Iqbal of the Middle Eastern Department and Abbas Mirakhor of the Research Department. To collect information and views for the study, the authors held discussions with the authorities and representatives of commercial banks in the Islamic Republic of Iran and in Pakistan.